2017
DOI: 10.1021/acs.jpcb.6b11108
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Sized Water Bridge and Pull-Off Force in AFM at Different Relative Humidities: Reproducibility Measurement and Model Based on Surface Tension Change

Abstract: This article deals with the analysis of the relationship between the pull-off force measured by atomic force microscopy and the dimensions of water bridge condensed between a hydrophilic silicon oxide tip and a silicon oxide surface under ambient conditions. Our experiments have shown that the pull-off force increases linearly with the radius of the tip and nonmonotonically with the relative humidity (RH). The latter dependence generally consists of an initial constant part changing to a convex-concave-like in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…However, when RH > 23%, an adsorbed water layer begins to form and expands from the initial liquid island to the entire graphene surface, thereby increasing the F c and F a as RH rises to~45% [88]. Several other studies demonstrated that the increase of RH above 50% may result in a decrease of F a , especially on hydrophilic surfaces (Figure 10c) [80,81,93]. Xiao and Qian [80] built a new formulation to fit this complex RH-dependent adhesion behavior and explain the observed decrease in F a at high RH.…”
Section: Effect Of Water Condensation On Capillary Forcementioning
confidence: 94%
See 3 more Smart Citations
“…However, when RH > 23%, an adsorbed water layer begins to form and expands from the initial liquid island to the entire graphene surface, thereby increasing the F c and F a as RH rises to~45% [88]. Several other studies demonstrated that the increase of RH above 50% may result in a decrease of F a , especially on hydrophilic surfaces (Figure 10c) [80,81,93]. Xiao and Qian [80] built a new formulation to fit this complex RH-dependent adhesion behavior and explain the observed decrease in F a at high RH.…”
Section: Effect Of Water Condensation On Capillary Forcementioning
confidence: 94%
“…Chen et al [4] measured the F a on a hydrophobic H-terminated Si surface (water contact angle~83 • ) and found that the force decreases substantially as the test environment transits from humid air to liquid water. During this process, A Hamaker is reduced by 80% [80,85,93]. On a hydrophobic Si surface, water adsorption is very weak (Figure 5d), so F c is negligible and F vdW decreases, leading to a considerable decrease of F a .…”
Section: Effect Of Water Adsorption On Van Der Waals Forcementioning
confidence: 99%
See 2 more Smart Citations
“…This distance is the jump-to-contact distance D jtc and it will be determined by the mechanical instability of the cantilever when the electrostatic force is applied. If the cantilever is considered a harmonic oscillator, D jtc can be obtained from K=dF elec /dD where K is the spring constant and F elec the electrostatic force) It may also be produced by the formation of a water bridge between tip and sample 23 . The error increases when h increases and  decreases and it vanishes when h→0 and →∞.…”
Section: Theoretical Simulationsmentioning
confidence: 99%